Stenosing tuberculous enteritis, occlusion - Liard, Washington; Albo Volonté, Manuel; Niski de Rydel, Rosa; Cassinelli, J F (Cirugía del Uruguay, 2020)
A case of mecanic obstruction of the small bowell is reported. Laparatomy disclosed: great dilatation of the small bowell due to circular stricture; the procedure was resection follow by end to end anastomosis. The histologycal study revealed tuberculosis and the presence of Corynebacterium Tuberculosis. The etiology was reassured · by typical roentgenologic changes in both lungs. The frecuency and the current status of the diagnosis of intestinal tuberculosis are discussed.